Kreuzer, Gundula. 2018. Curtain, Gong, Steam: Wagnerian Technologies of Nineteenth-Century Opera. Oakland, CA: University of California Press. - Rothe, Alexander K. (Current Musicology, 2018)
In a recent Journal of the American Musicological Society colloquy, “Discrete/Continuous: Music and Media Theory after Kittler,” Alexander Rehding argues that the late Friedrich Kittler’s media theory—and its subsequent development by media theorists after Kittler (Sybille Krämer, Bernhard Siegert, Wolfgang Ernst, Jussi Parikka)—has a great deal to offer current musicology (Rehding et al. 2017, 225). Despite criticisms from Geoffrey Winthrop-Young (2002, 832) that Kittler adheres to a form of technologi-cal determinism, and focuses too narrowly on the connection between me-dia technologies and the military-industrial complex, Rehding claims that Kittler’s media theory can nevertheless help musicologists make sense of the material and technological underpinnings of music and sound.